Coteaching as perceived by special education and regular education teachers - Chiang, Li-Fen (Lily) (Animo Repository, 2002)
This study determines the perceptions of special education and general education teachers on co-teaching. The study employed the descriptive type of research utilizing a researcher-made questionnaire consisting of two parts, namely: Part I - Personal Information and Part II - Perceptions on Co-teaching. The participants of the study were 60 teacher, 30 of whom are from special education setting and another 30 are from the general education setting. The study revealed that most of the special education teachers and regular education teachers are qualified to teach children with special needs and typically developing children, respectively based on their educational background and experiences. Special education teachers' perceptions on co-teaching practices relative to the eight components of co-teaching, were often in consonance with the nature and principles of co-teaching. On the other hand, the regular education teachers' perceptions on co-teaching perceptions relative to interpersonal communication skills physical arrangement and instructional presentation need to be modified. However, for the rest of the eight components they concur with the nature and principles of co-teaching. Special Education teachers prefer the interactive teaching model while majority of the regular education teachers did not have any preferences. The regular education teachers are not ready for inclusion while the special education teachers need to enhance their attitude towards co-teaching.